PENGARUH PEMANFAATAN FASILITAS BEAJAR, DISIPLIN BELAJAR, DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG - Mifta Rizka; Idris Idris (Program Magister Pendidikan Ekonomi (S2), 2016)
This article aims to informed and saw the effect of learning facilities utilization, learning discipline and learning motivation of the students' learning outcomes in Economic Faculty Padang State University.This research is and associative.The study population all students Stata 1 Grade 2012-2014 of Economic Faculty Padang State University 1344 people, the number of samples 364 people.The sample collection technique proportionally stratified random sampling.Data and data sources are primary data and secondary data. The test instrument validity and reliability.Analyzed using descriptive and inductive analysis. The results showed that: 1) Facilities utilization learning significantly and contribution influence student learning discipline 2) Learning discipline significantly and contribution influence learnign,3) Facilities utilization learning, learning discipline and learning motivation have a significant and contribution on students' learning outcomes in Economic Faculty Padang State University. Keywords: Learning Facility Utilization, Learning disciplibe, learning motivation, and Learning Outcomes